PENGARUH PEMBIASAAN SHALAT BERJAMAAH TERHADAP AKHLAK SANTRI PONDOK PESANTREN TAHFIDZUL QUR’AN DARUL HIKAM MANCAR PETERONGAN JOMBANG - Khoirul Huda; Adibah Adibah; Bayu Astino (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
This research aims to determine the effect of the habit of praying in congregation on the morals of students at the Tahfidzul Qur'an Darul Hikam Mancar Peterongan Jombang Islamic Boarding School. This type of research is quantitative, data collection is through interviews, questionnaires, observation and documentation. The data analysis uses a simple linear regression statistical formula and tests the significance of the influence of the habit of congregational prayer on the morals of the students. The results of the research showed that based on a questionnaire regarding students' habit of praying in congregation, the percentage was 59%, the questionnaire on the morals of students was 53.67%, which means that the students' morals were classified as good. From the results of statistical calculations, the influence of the variable habitual prayer in congregation on the morals of the students of the Tahfidzul Qur'an Darul Hikam Islamic Boarding School was found to be 89.8% and the remaining 10.2% was influenced by other factors. So there is a significant influence of the habit of praying in congregation on the morals of students at the Tahfidzul Qur'an Darul Hikam Mancar Peterongan Jombang Islamic Boarding School.